Perception of the quality of life of elderly people in senior centers in Cuiabá, Mato Grosso - Rodrigues, Dayane de Carvalho; Espinosa, Mariano Martínez; Marcon, Samira Reschetti; Alves, Bryan Mariano Martínez (HSJ, 2020)
Introduction: The change in the demographic profile in the world scenario, and the most recent form in Brazil, has among its manifestations, the increase in the number of the elderly population. This increase needs to be accompanied by improved and maintained health and quality of life. Aims: To evaluate the perception of quality of life of elderly people participants of the Social Centers of the city of Cuiabá, Brazil. Methods: Cross-sectional study with 317 elderly participants of the Senior Centers of the city of Cuiabá, conducted from July to December 2012. For data collection used a sociodemographic questionnaire and WHOQOL-BREF and WHOQOL OLD. They used the Mann-Whitney and Kruskal-Wallis tests. Results: The sample was composed mostly of women, aged 60 to 69 years, illiterate, without a partner and with income less than or equal to one minimum wage. The domains with the lowest scores were environment and sensory functioning, while the highest domains were psychological and death and dying. Conclusion: In general, the elderly people had a good quality of life, revealing that the Senior Centers can be a promising alternative for improving the health conditions and quality of life of the elderly.